G Protein-Coupled Receptor Kinase 2 as Novel Therapeutic Target in Fibrotic Diseases - Li, Nan; Shan, Shan; Li, Xiu-Qin; Chen, Ting-Ting; Qi, Meng; Zhang, Sheng-Nan; Wang, Zi-Ying; Zhang, Ling-Ling; Wei, Wei; Sun, Wu-Yi (Frontiers in Immunology, 2022)
G protein-coupled receptor kinase 2 (GRK2), an important subtype of GRKs, specifically phosphorylates agonist-activated G protein-coupled receptors (GPCRs). Besides, current research confirms that it participates in multiple regulation of diverse cells via a non-phosphorylated pathway, including interacting with various non-receptor substrates and binding partners. Fibrosis is a common pathophysiological phenomenon in the repair process of many tissues due to various pathogenic factors such as inflammation, injury, drugs, etc. The characteristics of fibrosis are the activation of fibroblasts leading to myofibroblast proliferation and differentiation, subsequent aggerate excessive deposition of extracellular matrix (ECM). Then, a positive feedback loop is occurred between tissue stiffness caused by ECM and fibroblasts, ultimately resulting in distortion of organ architecture and function. At present, GRK2, which has been described as a multifunctional protein, regulates copious signaling pathways under pathophysiological conditions correlated with fibrotic diseases. Along with GRK2-mediated regulation, there are diverse effects on the growth and apoptosis of different cells, inflammatory response and deposition of ECM, which are essential in organ fibrosis progression. This review is to highlight the relationship between GRK2 and fibrotic diseases based on recent research. It is becoming more convincing that GRK2 could be considered as a potential therapeutic target in many fibrotic diseases.